Mother, Service User, and Social Worker - Polar, Brenda (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
In this article, I share some of my parenting experiences and reflections on being a mother, child services user, and mental health service provider. I have two aims: to bring visibility to some of the issues that marginalized mothers, such as single immigrant mothers and Indigenous mothers, may experience when accessing support services; and to call on social workers to reflect on our attitudes in our work with racialized immigrant mothers and Indigenous mothers. This article is informed by decolonial and borderlands theories. In the first section, I focus on the marginalization of racialized mothers through my own mothering experiences as a racialized mother of two children and the expectations put on single mothers. In the second section, I discuss my experiences as a mother and service user attempting to access support services. I analyze the influences of white heteropatriarchal and neoliberal ideologies in shaping parenting support services and the surveillance in those practices. In the third section, I connect my experiences as a mother and service user with my conflicting role as a service provider. There were many complexities involved in my position as a racialized immigrant mental health worker. My experience as a social worker while being a service user and mother informs my argument that demands made of service users are often unrealistic and there is very little support offered to meet these demands. I suggest that service providers step out of their social worker role and, as individuals, question their demands of service users and how reasonable they are, based on the situation and the location of the service user. The person on the line let me know that I was going to be a mom. The news came unexpectedly. I sat on my chair. I could not feel my hands. I was lost as to what to do next. I was going to be a single mom in a city that was unfamiliar to me, and I was clueless as to what being a mom meant. I was a knot of excitement, panic, and happiness.